Liliendaal declaration on agriculture and food security (2011)
Text of the Liliendaal Declaration on Agriculture and Food Security emanating from the Thirtieth Meeting of the Conference of Heads of Government of the Caribean Community, Liliendaal, Guyana, 2-5 July 2009.
Keywords: AGRICULTURE